Aid Effectiveness : A Survey of the Recent Empirical Literature - Tsikata, Tsidi (Washington, D.C. : International Monetary Fund, 1998)
The preponderance of evidence from the empirical literature on aid effectiveness suggests that development aid has not had a significant impact on growth in recipient countries. However, there is some evidence that aid has had positive effects when the policy environment has been conducive to growth. Regarding the relationship between aid and the main channels through which its impact on growth could flow-investment and domestic saving-the evidence is mixed, with some indication that aid has had a positive impact where adjustment efforts have been sustained.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet